Evidence-informed stakeholder consultations to promote rights-based approaches for children with disabilities - Shikako, Keiko; Lai, Jonathan; Yoo, Paul Y.; Teachman, Gail; Majnemer, Annette (Frontiers in Rehabilitation Sciences, 2024)
Purpose: To strengthen the translation of evidence to actionable policy, stakeholder engagement is necessary to synthesize, prioritize and contextualize the academic research content into accessible language. In this manuscript, we describe a multi-level evidence-based stakeholder consultation process and related outcomes proposed to promote awareness of and foster cross-sectorial collaborations toward human rights-based approaches for children with disabilities. Methods: Mixed-methods participatory action research done in three steps: 1.A literature review of peer-reviewed evidence on rights-based approaches in childhood disabilities; 2.Consultation with researchers in diverse fields, grassroot organizations, caregivers, and youth with disabilities; 3. A constructive dialogue with decision makers at federal and provincial levels in Canada to discuss consultations results. Results: Stakeholders value human rights approaches that can have a direct impact on practical aspects of their daily living. Organizations give high importance to adopting rights-based approaches to measure policy outcomes, while parents value service provision and youth emphasize opportunities for belonging and accessibility to community and daily life activities. Conclusion: The implementation of rights-based approaches in childhood disabilities can support policy, services, and daily lives of children with disabilities and the ecosystems around them. It can also guide research priorities, and create a common language to foster collaborations across sectors and interested parties.